Dukungan Sosial dan Religiusitas Dalam Penyesuaian Diri Mahasiswa Perantau - Supriyadi, Tugimin; Widyastuti, Mega; Salsabilla, Aulia Yasmin; Widjanarko, Mochamad (Universitas Muria Kudus, 2024)
This study aims to determine whether there is an influence of the variables Social support and Religiosity on Self Adjustment in students who migrate to Bekasi. Based on the phenomenon that migrant students will always meet, interact, and communicate with fellow migrants and the native community, it will cause cultural diversity and changes in students so that the demands to adjust themselves increase. In order to be able to carry out good Self Adjustment in a migrant state, Social support and Religiosity may have an influence. This study has three hypotheses, namely there is an influence between Social support and Self Adjustment in students who migrate (H1); there is an influence between Religiosity on the relationship between Self Adjustment in students who migrate (H2); and there is a relationship between Social support and Religiosity on Self Adjustment in students who migrate (H3). The research method used is quantitative with a descriptive approach. Based on the results of this study, it can be concluded that there is an influence between Social support and Self Adjustment; there is no influence between Religiosity and Self Adjustment; and there is an influence between Social support and Religiosity on Self Adjustment in migrant students in Bekasi.Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh pada variable social support dan religiosity terhadap self adjustment pada mahasiswa yang merantau di Bekasi. Berdasarkan fenomena bahwa mahasiswa perantau akan selalu bertemu, berinteraksi, dan menjalin komunikasi dengan sesama perantau dan masyarakat asli sehingga akan menimbulkan keanekaragaman budaya dan perubahan pada diri mahasiswa sehingga tuntutan untuk menyesuaikan diri semakin meningkat. Untuk dapat melakukan self adjustment yang baik di perantauan, social support dan religiosity mungkin mempunyai pengaruh. Penelitian ini memiliki tiga hipotesis, yaitu terdapat pengaruh antara social support dengan self adjustment pada mahasiswa yang merantau (H1); terdapat pengaruh antara religiosity terhadap hubungan self adjustment pada mahasiswa yang merantau (H2); dan terdapat hubungan antara social support dan religiosity terhadap self adjustment pada mahasiswa yang merantau (H3). Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan deskriptif. Berdasarkan hasil penelitian ini, dapat disimpulkan bahwa terdapat pengaruh antara social support terhadap self adjustment; tidak terdapat pengaruh antara religiosity terhadap self adjustment; dan terdapat pengaruh antara social support and religiosity terhadap self adjustment pada mahasiswa perantau di Bekasi.